Gamification-Engagement-Loyalty for Digital Consumer Behavior - Lasmy; Idris Gautama So; Muhammad Shabir Shaharudin (Universitas Pendidikan Ganesha, 2026)
The increasing popularity of gamification strategies in marketplace platforms has led to a growing need for research on their effectiveness. Despite the growing number of gamification implementations, there is still a lack of research on the impact of gamification on customer engagement and loyalty in marketplace platforms. This study aims to fill this research gap by investigating the effectiveness of gamification strategies in improving customer engagement and loyalty in marketplace platforms. This research examines how to measure the effect of gamification on customer engagement and consumer loyalty in the Shopee marketplace platform on the DKI Jakarta users. Digital platforms are increasingly leveraging gamification to help retain users; this is a process where non-game activities are designed to include elements from video games like challenges, rewards, and interactive elements. By employing a quantitative method and examination of the survey results from 416 Shopee customers by using SmartPLS software, this study reveals that gamification has a substantial influence on customer engagement. At the same time, increased engagement significantly increases the consumer loyal-ty, which implies a strong mediating relationship. While gamification per se directly contribute to customer loyalty, its impact is increased significantly when engagement is considered as a mediating variable. These results indicate that gamification is not only a service packaging tool used for user entertainment or attracted purposes, but also a strategic force to reinforce the user relationship, the shopping satisfaction, the long-term benefit, etc. Consequently, marketplace platforms are in-centivized to build creative and customized gamification features for sustained commercial value.